2020
DOI: 10.1002/ijfe.2143
|View full text |Cite
|
Sign up to set email alerts
|

The impact of FDI on income inequality: Evidence from the perspective of financial development

Abstract: By considering the threshold effects of different financial indicators, the current study investigates the relationship among income inequality, foreign direct investment (FDI), and financial development (FV) for a sample of 37 countries over the period 2001-2015. Using the panel smooth transition regression (PSTR) model, the empirical results indicate that FDI helps to reduce income inequality, but this beneficial effect becomes weak when the country has reached a threshold level of financial development. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 61 publications
(85 reference statements)
4
26
0
1
Order By: Relevance
“…To minimize errors in the regression results from the omission of variables, the following control variables are selected to the models. Economic development ( lnGDP ) is expressed by the regional GDP, while foreign direct investment ( lnFDI ) can stimulate green innovation in local industries because foreign companies bring capital and advanced technologies (Gao et al 2021 ; Lee et al 2022 ). Using the weight of industrial added value in regional GDP, the industrial structure ( lnIS ) significantly improves energy efficiency (Long et al 2016 ).…”
Section: Methodology and Datamentioning
confidence: 99%
“…To minimize errors in the regression results from the omission of variables, the following control variables are selected to the models. Economic development ( lnGDP ) is expressed by the regional GDP, while foreign direct investment ( lnFDI ) can stimulate green innovation in local industries because foreign companies bring capital and advanced technologies (Gao et al 2021 ; Lee et al 2022 ). Using the weight of industrial added value in regional GDP, the industrial structure ( lnIS ) significantly improves energy efficiency (Long et al 2016 ).…”
Section: Methodology and Datamentioning
confidence: 99%
“…In recent literature, FDI and inequality are framed in the same picture and have gained remarkable popularity. In this connection [ 10 , 11 ], disclose that FDI contributes significantly to determining inequality. Conversely, the studies conducted by [ 12 , 13 ] argued that FDI did not take part in the variation of inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, in another study on Sub-Saharan African countries, Anetor et al (2020) concluded that FDI inflows exert an inverted-U impact on poverty and the Sub-Saharan African nations are yet to attract the threshold level of FDI required to ensure reduction in their respective poverty levels. Furthermore, as far as the FDI inflows-Gini index nexus is concerned, Lee et al (2020) and Xu et al (2021) recently argued that FDI inflows are effective in curbing the Gini index in the case of 37 global economies and Sub-Saharan African nations, respectively. Summing up, the majority of the studies conclude that FDI significantly mitigates the adverse repercussions of poverty.…”
Section: Literature Reviewmentioning
confidence: 99%